Contralesional subjective visual horizontal predicts endolymphatic hydrops. (1st October 2020) - Nham, Benjamin; Welgampola, Miriam S.; Halmagyi, G. Michael
Abstract: Background: The subjective visual horizontal (SVH) is a test of utricular function that assesses conjugate ocular torsion which is a component of the ocular tilt reaction (OTR). In unilateral destructive peripheral vestibular lesions, the OTR and so the SVH tilt is usually ipsiversive. Aims/objective: Our study aimed to profile the causes of a contraversive SVH tilt in patients with a confirmed unilateral peripheral vestibular deficit. Materials and methods: The clinical records, nystagmus and vestibular investigation characteristics of 52 patients with a unilateral canal paresis (CP) on caloric of ≥30%, a contraversive SVH tilt of ≥4 degrees and at least one pure tone audiometry were retrospectively analysed. Results: The most common diagnosis of patients ( n = 39) with a contraversive SVH and ipsilesional CP was endolymphatic hydrops: 35 (67.3%) had Meniere's disease (MD) and 4 (7.7%) had delayed endolymphatic hydrops (DEH). The remaining 13 (25%) of cases had other peripheral aetiologies or an unknown diagnosis. 16 (30.8%) patients had ictal spontaneous nystagmus at the time of SVH or caloric testing. Conclusions and significance: A contraversive SVH with unilateral CP suggests endolymphatic hydrops.